Priority needs for improvement of activity data to support MRV in Ethiopia’s livestock sector - Wilkes, Andreas; Wassie, Shimels Eshete; Baker, Derek (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To complement an ongoing CCAFS project ‘Enhancing capacities for MRV of sustainable livestock action in East Africa (Kenya and Ethiopia)’, implemented by UNIQUE forestry and land use, ACIAR is supporting CCAFS to implement a Small Research Activity (SRA) entitled ‘Building capacities for an integrated livestock MRV system in Ethiopia’. The objective of the SRA is to support improvements in methods and procedures used to produce and manage the livestock activity data required for measurement, reporting and verification (MRV) of greenhouse gases (GHG) in Ethiopia. The focus will be on administrative data that is needed for periodic MRV (including both the GHG inventory and mitigation reporting), and data gaps that can be filled through surveys. The SRA will be implemented between June 2019 and the end of December 2020. This report is the first deliverable under the SRA and describes the priority needs for improvement of livestock activity data in Ethiopia’s national MRV systems.